Raynaud’s Phenomenon: A Brief Review of the Underlying Mechanisms - Fardoun, Manal M.; Nassif, Joseph; Issa, Khodr; Baydoun, Elias; Eid, Ali H. (Frontiers in Pharmacology, 2016)
Raynaud's phenomenon (RP) is characterized by exaggerated cold-induced vasoconstriction. This augmented vasoconstriction occurs by virtue of a reflex response to cooling via the sympathetic nervous system as well as by local activation of α2C adrenoceptors (α2C-AR). In a cold-initiated, mitochondrion-mediated mechanism involving reactive oxygen species and the Rho/ROCK pathway, cytoskeletal rearrangement in vascular smooth muscle cells (VSMCs) orchestrates the translocation of α2C-AR to the cell membrane, where this receptor readily interacts with its ligand. Different parameters are involved in this spatial and functional rescue of α2C-AR. Of notable relevance is the female hormone, 17β-estradiol, or estrogen. This is consistent with the high prevalence of RP in pre-menopausal women compared to age-matched males. In addition to dissecting the role of these various players, the contribution of pollution as well as genetic background to the onset and prevalence of RP are also discussed. Different therapeutic approaches employed as treatment modalities for this disease are also highlighted and analyzed. The lack of an appropriate animal model for RP mandates that more efforts be undertaken in order to better understand and eventually treat this disease. Although several lines of treatment are utilized, it is important to note that precaution is often effective in reducing severity or frequency of RP attacks.